Literature Review: Analysis of Factors Related to User Satisfaction on The Online Reference System for BPJS Health Participants in Semarang City - Fadhilla Rahma Jodi Putri (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
An online referral system is an innovation from BPJS Health in digitizing the tiered referral system. An online referral system is expected to increase the participants' satisfaction and convenience in obtaining the referral service. However, there was no evaluation in satisfaction measurement on an online referral system until this time, especially in Semarang City. This study aims to evaluate the implementation of an online referral system by analyzing factors related to the satisfaction of BPJS Health participants in Semarang City. This was a quantitative research with a cross-sectional approach involving 100 respondents chosen by accidental sampling technique. The results of the study showed that the percentage of respondents who felt satisfied was only 54%, which was caused by the administrative efficiency and system effectivity of an online referral system that is still not optimal in reducing queues. Besides that, there is a relationship between performance expectancy, effort expectancy, facilitating condition, information quality, and user satisfaction towards the implementation of an online referral system in the BPJS Health of Semarang City with a p-value < 0,05. The results of the study suggest for BPJS Health determine the participants' satisfaction indicators towards the implementation of the online referral system and integrate the online referral system with the registration system at secondary and tertiary health facilities in Semarang City.